Kesulitan Guru Ips Dalam Pemberian Penugasan Project Dalam Penerapan Kurikulum Merdeka - Situmorang, Romauli; Purba, Rosma; Simbolon, Kurnia; Sianipar, Maria Dwi; Sidauruk, Tumiar (Universitas Lampung, 2024)
This study discusses the difficulties faced by social studies teachers in providing project assignments in implementing the independent curriculum. This statement explains that the Independent Curriculum is an approach that provides freedom and independence to teachers and students in creating a meaningful learning process. The data collection technique used is by distributing questionnaires to be filled in by respondents. The results showed that social studies teachers faced several difficulties, such as lack of technical ability, lack of time, and lack of support from the school. With this study, researchers hope to contribute to the development of an independent curriculum and improve the quality of education in Indonesia